2019
DOI: 10.4103/aam.aam_27_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of traumatic dental injury to the anterior teeth in children attending paramilitary and nonparamilitary schools in Nigeria

Abstract: Objective: The objective of this study was to determine the prevalence of traumatic dental injuries (TDIs) in the anterior teeth among children attending paramilitary and nonparamilitary schools in Benin City, Nigeria. Materials and Methods: A multistage sampling technique was used to select children aged 8–12 years with a previous history of trauma to the orofacial region. A self-administered questionnaire was then applied, and each participant was examined clinically.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 17 publications
4
15
1
4
Order By: Relevance
“…2 The main causes of dental trauma were fights and falls which is similar to reports from other countries. 26,27 The results of this study revealed insufficient knowledge of teachers regarding dental trauma which is in line with previous studies nationally and internationally. Although almost half of the participants had witnessed dental trauma, only 7.2% were able to manage it.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…2 The main causes of dental trauma were fights and falls which is similar to reports from other countries. 26,27 The results of this study revealed insufficient knowledge of teachers regarding dental trauma which is in line with previous studies nationally and internationally. Although almost half of the participants had witnessed dental trauma, only 7.2% were able to manage it.…”
Section: Discussionsupporting
confidence: 89%
“…Although the prevalence of traumatic injuries varies worldwide due to geographical locations, demographics, causes of traumatic injury and the study methodology, the prevalence in the current study was within the range of 7% to 59% reported by different studies 2 . The main causes of dental trauma were fights and falls which is similar to reports from other countries 26,27 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…There was a 1.9% prevalence of anterior tooth traumatic injury, for which a proportionate number were males. Traumatic dental injury was found to have occurred in 11.4% of a school population in Nigeria, 30 18.5% in a 3- to 5-year-old Sudanese population, 31 and 9.3% in a 12-year-old Indian population. 32 This study, however, reports the prevalence of individuals with evidence of anterior traumatic injury, thus excluding individuals who might have had a traumatic dental injury without necessarily having any sign or symptom, as demonstrated in other studies.…”
Section: Discussionmentioning
confidence: 96%
“…The distribution of dental injuries according to the classification of Ellis modified by Fried showed that the most common type of injury was enamel fracture (51.6%), followed by enamel and dentine (36.1), then enamel and dentine with extensive exposure of pulp (7.1%), then fracture involving complete loss of tooth (avulsion) (2.6%),followed by enamel and dentine with early exposure of pulp (1.9%) , and finally a root fracture (0.6%) and no statistical significant difference between them and gender ( Table 5). 22 . The difference in TDI prevalence is associated with many factors for instance study design, sample size, sampling procedure, diagnostic criteria, limited age groups, geographical differences and study locations 23 .…”
Section: Discussionmentioning
confidence: 99%